Pengaruh Metode Debat Terhadap Keterampilan Berpikir Kritis Siswa di Kelas III SDN 124388 Pematangsiantar T.A 2023/2024 - Christin Angelita Sianturi (STIKes Ibnu Sina Ajibarang, 2024)
The problem in this study is the lack of critical thinking skills of students. This can be seen from the activeness of students in the learning process in the classroom, where out of a total of 40 students only 10 students are active in learning, both asking and answering questions in the learning process, while the other 30 students are not active in the learning process, or passively do not ask or answer questions (<60). This is caused by teachers assessing students and providing information orally through lectures. The use of this conventional learning model results in a passive and less conducive classroom atmosphere, students often lose focus on learning, and as a result, students' creative thinking is very low because many students find it difficult to convey opinions or answers about the material . This research was conducted at SDN 124388 Pematangsiantar using an experimental type. (esperimental research) is a quasi-quantitative research approach (Quasi Experimental Design). The subject of this study is grade III students, consisting of 2 classes divided into an experimental group and a control group, with a total of 40 students. The object of this research is students' critical thinking skills using the debate method. Data was collected through a test in the form of a questionnaire consisting of 12 questions. The results of the t test calculation show a significance value of p (sig (2-tailed)) of 0.000. Because the p value is less than 0.05, the null hypothesis (Ho) can be rejected and the alternative hypothesis (Ha) can be accepted. Thus, it can be concluded that there is an effect of the application of the debate method on students' critical thinking skills at SDN 124388 Pematangsiantar. Based on the above analysis, it can be concluded that the use of the debate method can improve students' critical thinking skills with the subject of identifying diversity in the PPKN learning subjects as evidenced by the average listening skills in the pretest in the experimental class or the class that received treatment, which was 34.4 increased in the posstest to 41.8. Thus, the researcher suggests that teachers can use the debate method in learning.